Organic Semiconductors for Transparent Electronics - Usta, Hakan; Facchetti, A. F. (wiley, 2018)
A relatively unexplored, yet important, research focus has been to develop optically transparent organic semiconductor thin films with efficient charge-transport characteristics. This chapter focuses on transparent organic semiconductors. Organic thin-film transistors (TFTs) are envisioned as key building blocks of next generation electronic technologies such as low-power-consumption flexible displays, electronic papers, plastic RFID tags, and sensors. The historic development of oligothiophene derivatives has significantly advanced the field of organic semiconductors for organic TFT and achieved record charge carrier mobilities for both hole and electron. In the past decade, organic semiconductor research has extensively focused on fused heteroacenes as a new promising class of p-type semiconductors. Rylene dicarboximides belong to one of the most popular and deeply studied classes of n-type semiconductors. Among the rylene dicarboximide semiconductors developed in the past two decades for organic electronics, only pyromelliticdicarboximides (PyDI) and naphthalenedicarboximides (NDI) have the potential for use in transparent electronics. © 2025 Elsevier B.V., All rights reserved.
Keywords: Fused Heteroacenes; Naphthalenedicarboximides; Oligothiophene; Organic Thin-Film Transistors; Pyromelliticdicarboximides; Rylene Dicarboximide; Transparent Electronics